Differences and Similarities in Motives to Decrease Drinking, and to Drink in General Between Former and Current Heavy Drinkers—Implications for Changing Own Drinking Behaviour - Rowicka, Magdalena (Frontiers in Psychology, 2022)
The evidence on why people initiate or cease drinking is vast; however, little is known why people change their frequency and amount of drinking from intense (heavy or dependent drinking) to recreational one (with little risk). Therefore, the purpose of this study was to investigate how drinking motives, as well as motives to decrease drinking, differ between former heavy drinkers (problematic and dependent), current dependent and current recreational drinkers. Data were obtained from four groups of individuals (n=263) using alcohol with different severity. The participants were Polish young adults aged between 18 and 35. 53% of the sample were women. AUDIT was used to assess the level of drinking; the Drinking Motive Questionnaire-Revised Short Form (DMQ-R SF) was used to assess drinking motives (social, coping, enhancement and conformity). Additionally, a set of questions regarding motives to decrease drinking were analysed. RALD instrument was used to assess reasons for abstaining and limiting drinking. The results show that differences were observed between the investigated groups: the current dependent group scored significantly higher on all the dimensions of drinking motives than the current low-risk group and significantly higher on coping, social and enhancement motives than former heavy drinkers (both groups). The two groups of former heavy drinkers did not differ from each other on drinking motives. The investigated groups differed on the motives to reduce drinking – low-risk users scored the lowest on all the motives, whereas current dependent – the highest. The differences in motive to decrease drinking between current depended and former heavy drinkers indicate which motives can be associated with prevention strategies, programs, and therapeutic approaches.